Murine models of glycoprotein Ib-IX - Jerry Ware (Platelets, 2022)
The utility of mouse models to dissect the molecular basis of hemostasis and thrombosis is now well established. The anucleate properties of circulating blood platelet and their specialized release from mature megakaryocytes makes the use of in vivo models all the more informative and powerful. Indeed, they are powerful but there do exist limitations. Here, we review the contributions of mouse models to the pathogenesis of the Bernard–Soulier syndrome, their use in platelet-specific gene expression, the recent development of mice expressing both human GPIb-IX and human von Willebrand factor (VWF), and finally the use of GPIb-IX mouse models to examine the impact of platelet biology beyond clotting. The humanization of the receptor and ligand axis is likely to be a major advancement in the characterization of therapeutics in the complex pathogenesis that drives thrombosis. When appropriate, we highlight some limitations of each mouse model, but this is not to minimize the contributions these models to the field. Rather, the limitations are meant to provide context for any direct application to the important mechanisms supporting human primary hemostasis and thrombosis.